2000
DOI: 10.1177/154193120004403214
|View full text |Cite
|
Sign up to set email alerts
|

Affordance Perception and Safety Intervention

Abstract: The notion that people consider accident risk during driving and other activities has long dominated safety research. The practical importance of risk perception and risk compensation, however, has been overrated. As an alternative formulation, behavior may be affected by action-oriented perception of affordances — we act in ways that we think will be adequate for success. Research on affordance perception has implications for understanding the causes of accidents, and for evaluating and designing warnings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
(3 reference statements)
0
19
0
Order By: Relevance
“…Thus, it is likely that many of the sledders we observed, who were using the same or similar products as the exemplars, were provided with the same or similar warnings. Ayres et al (2000) noted that people are unlikely to engage in behaviors with very likely or severe consequences. The low usage rates we observed, despite the prevalence of helmet use warnings, suggest that sledders generally do not perceive head injury to be a likely or severe consequence of sledding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that many of the sledders we observed, who were using the same or similar products as the exemplars, were provided with the same or similar warnings. Ayres et al (2000) noted that people are unlikely to engage in behaviors with very likely or severe consequences. The low usage rates we observed, despite the prevalence of helmet use warnings, suggest that sledders generally do not perceive head injury to be a likely or severe consequence of sledding.…”
Section: Discussionmentioning
confidence: 99%
“…The low usage rates we observed, despite the prevalence of helmet use warnings, suggest that sledders generally do not perceive head injury to be a likely or severe consequence of sledding. Decisions regarding helmet use are likely to be based on the immediate perceived affordances of sledding, and the resultant behaviors are believed to be generally adequate for success (Ayres et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed also that agricultural machinery operators often disregard the steepness of terrain [13,14,15] and they tend to be inaccurate when estimating slopes [5,14]. This may lead to driving in hazardous conditions, thereby increasing the risk of a rollover incident [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, one implication of this finding is that it demotes the role of risk perception and assigns a far stronger role to supraindividual factors likely to influence the expression of unsafe behaviors. Finally, Ayres, Wood, Schmidt and McCarthy [11] and Ayres, Wood, Schmidt, Young, et al [28] assert that the practical importance of risk perception has been overstated. They distinguish between risk judgments and risk perception and suggest that in experimental studies, people can be cued into providing reasonably accurate risk judgments but "this does not necessarily mean that people perceive risk" (p. 36) [11].…”
Section: Introductionmentioning
confidence: 99%